INFORMATION TECHNOLOGY ADOPTION: THE EMERGENCE OF NEW COMPETENCIES AND ACTORS - Dyakova, Elena Grigorevna; Trakhtenberg, Anna Davidovna (Nauka Krasnoi͡a︡rʹi͡a, 2016)
When speaking about e-government, public officials proceed from the idea of drastic rupture with the conventional forms of government administration, using so called “rupture talk”. “Rupture” means that adoption of information technologies must entail fundamental changes in the relations between the citizens and the government including citizens’ empowerment. Operationalisation of “e-government” is performed via the concept of “e-services”. E-services are conceived in the logic of exclusion as a preemptive (and eventually designed to completely replace) traditional forms of interaction between citizens and public officials. The results of empirical research (focus groups, conducted in 2010 and 2015 in Ekaterinburg, Sverdlovsk Region) show that the citizens operationalize the e-government by other logic – the logic of inclusion. They use new ways of interaction with the government for solution of conventional problems. Even though they express willingness to use the e-services, real decisions are made at the situational level – they choose whether to use the new or old rules depending on the significance of the particular problem. Electronic interaction is perceived by them as secondary, ancillary, providing no fundamental change in their relations with the public officials. Citizens are actors, applying a set of competencies, rather than passive users, operating in a strictly defined framework. Purpose. The article is devoted to the study of information technology adoption in the field of interaction between citizens and public authorities. The subject of the analysis is the citizens’ use of state and municipal e-services. The authors aim to show that the citizens are not passive users but actors, converting e-services in accordance with their own interests. Methodology. The basis of the research is the results of two focus groups conducted in 2010 and 2015 in one of the Russian industrial areas and its central city. Methodologically the authors proceed from the principles of the theory of social construction of technology (SCOT). Results. The authors show that citizens in the process of interaction with the authorities form their own “arch of action”, in the core of which are the traditional forms of citizens – officials interaction, focused on personal communication with the officials. Electronic interaction plays a purely functional, subordinate role. It is used for solving a number of preparatory tasks (to define a set of required documents, make an appointment, etc.). The authors conclude that the actual practice of e-services use diverge from normative ideas about how such interaction should look in the concept of e-government. Practical implications. The research results can be applied in the field of public administraion and design of state and municipal e-services.